Assessing synergies: a case study of Zillow and Trulia - McDonald, Michael (Henry Stewart Talks, 2016)
Mergers and acquisitions, Valuing synergies, What drives synergies, Zillow and Trulia: overview, Zillow and Trulia: merger, Zillow and Trulia: before and after